Self-reported adherence to HIV/AIDS management and associated factors among gender-groups at a referral treatment centre in Port Harcourt, Nigeria - Luke, Anwuri; Owhonda, Golden; Tobin-West, Charles (International Journal Of Community Medicine And Public Health, 2022)
The self-reported method of assessing adherence levels among human immuno-deficiency virus (HIV)-positive patients is the most commonly applied measure, despite its limitations with recall bias and overestimation of outcome variables. This study determined the levels of self-reported adherence to HIV/AIDS management and its associated factors among gender groups at a referral treatment centre in Port Harcourt, Nigeria. This cross-sectional study was conducted among HIV-positive adults attending the University of Port Harcourt Teaching Hospital between September 2020 to November 2020. Systematic sampling technique was employed to select eligible participants using a 7-item brief medication self-reporting tool. Data was analysed with statistical package for social science (SPSS) version-25. Test of association was measured using Pearson’s Chi-square and spearman rho rank tests, set at a significance level of p<0.05 and 95% confidence interval. Confounding variables were controlled using multiple logistic regression analysis. 1600 participants; females (800), and males (800) were recruited. The mean age and standard deviation reported were; male (44.53±10.50), female (40.58±9.34). The mean self-reported optimal adherence levels observed were; male (98.7±6.4) and female (97.3±10.0). The significant variables associated with self-reported adherence levels were revealed only among the male group; religion (aOR=0.076; 95% CI=0.024-0.239; p<0.001), level of education (aOR=0.451; 95% CI=0.213-0.955; p=0.038), and non-payment for HIV support services (aOR=4.105; 95% CI; 1.712-9.792; p<0.001). The male group self-reported better optimal adherence than the female group. Also, the associated factors to self-reported adherence were only significant among the male group. Therefore, robust adherence counselling should be targeted at improving adherence among the female gender.